2012
DOI: 10.1136/sextrans-2011-050131
|View full text |Cite
|
Sign up to set email alerts
|

Supervised blood-based self-sample collection and rapid test performance: a valuable alternative to the use of saliva by HIV testing programmes with no medical or nursing staff: Table 1

Abstract: The study provides clear evidence that this methodology is a valuable alternative to saliva for HIV testing programmes when medical or nursing staff required to take blood samples is not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 5 publications
2
45
1
Order By: Relevance
“…Another 207 participants performed self-testing with the same materials, but after brief training and under the supervision of a counsellor. They participated in the procedure for interpretation of results described below, however, this methodology had a different objective, and the results with valid-invalid tests obtained with this supervised procedure have been presented elsewhere [25] and are not reported in the present study. Both designs were carried out during the same period but on different days.…”
Section: Methodsmentioning
confidence: 99%
“…Another 207 participants performed self-testing with the same materials, but after brief training and under the supervision of a counsellor. They participated in the procedure for interpretation of results described below, however, this methodology had a different objective, and the results with valid-invalid tests obtained with this supervised procedure have been presented elsewhere [25] and are not reported in the present study. Both designs were carried out during the same period but on different days.…”
Section: Methodsmentioning
confidence: 99%
“…Since then, this and other rapid HIV self-tests, have become available through pharmacies, online purchase, and, at times, through free distribution, in the U.S., Canada, and a number of European countries. Studies show high acceptability of self-testing among MSM [1827] and transgender women (TGW), who expressed particular interest in using it to test with sexual partners [28]. Studies have also shown that individuals are able to use oral as well as finger-prick rapid HIV tests correctly [26, 27] and that access to free self-tests leads to greater frequency of testing among MSM [29].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show high acceptability of self-testing among MSM [1827] and transgender women (TGW), who expressed particular interest in using it to test with sexual partners [28]. Studies have also shown that individuals are able to use oral as well as finger-prick rapid HIV tests correctly [26, 27] and that access to free self-tests leads to greater frequency of testing among MSM [29]. While the scientific literature on the acceptability and use of self-testing is increasing in relation to at-risk populations in the US, Europe and Africa, similar research among high risk populations in other regions of the world, including Latin America is in its infancy [25].…”
Section: Introductionmentioning
confidence: 99%
“…Pant Pai (2013) (9) Overall acceptability: 74% to 96% for both supervised and unsupervised settings (7,35,(43)(44)(45)(46)(47)(48)(49) (10,54,69) Overall: 47% to 100% (all US studies) (20,54,55,65).…”
Section: Linkage To Carementioning
confidence: 99%